A gendered analysis of family, work, social spheres and life satisfaction: The case of highly educated migrants in Hong Kong. (March 2023) - Man, Pui Kwan; Gan, Rebecca Yiqing; Fong, Eric
Migration is expected to bring higher life satisfaction with better social and economic achievement. While studies on life satisfaction treat migrants mainly as a single homogeneous group, knowledge about highly educated migrants is scant in current migration scholarship. Highly educated migrants may not have the higher life satisfaction because they may also have higher expectations. To complicate matters further, there may be gender differences in the experiences and life satisfaction of highly educated migrants. This study examines the factors associated with levels of life satisfaction among highly educated migrants from a gender perspective. First, we examine whether the level of life satisfaction differs by gender. Second, we explore various factors associated with the life satisfaction of highly educated migrants and whether these factors differ by gender. We examine these relationships using data from a respondent-driven sampling of 2, 884 highly educated Mainland Chinese migrants in Hong Kong. Our results indicate that the life satisfaction of female migrants is related to their social networks, whereas the life satisfaction of male migrants is related to economic security.